Enzymatic extraction of stevioside from Stevia Rebaudiana leaves using cellulase - Nasihah, Mohd Nor (2013)
Stevioside is one of the components known as diterpene glycoside existing in Stevia Rebaudiana leaves which have 250 to 300 sweeter than sucrose at the concentration of 0.4% (w/v). It is used as sweetening agents and taste modifier mostly in food industry. Moreover, stevioside has no calorific value and suitable used in therapeutic especially in treating diabetic people. The objective of this research is to extract the stevioside from Stevia rebaudiana leaves by using cellulase from Aspergillus Niger. The medium for enzyme used is acetate buffer while ethanol is applied as solvent in the enzymatic extraction of stevioside by performing various parameters such as concentration of enzyme, incubation time and temperature. Enzymatic extraction method gives the highest concentration of stevioside (900μg/ml) at 50°C as maximum temperature. The concentration of cellulase at 2% (w/v) gives the highest concentration of stevioside (830μg/ml) and the incubation times of 60 minutes gives the maximum time required to complete the extraction process of stevioside. Therefore, it can be concluded that the extraction of stevioside from Stevia rebaudiana leaves using cellulase is a new efficient way of obtaining high concentration of stevioside and also can minimize the use of solvent and energy consumption in degrading the cell wall.